'Better Beginnings has made me make reading part of our everyday routine': Mothers' Perceptions of a Family Literacy Program Over Four Years. Issue 4 (December 2015) - Barratt-Pugh, Caroline; Rohl, Mary
THIS PAPER EXPLORES THE Better Beginnings family literacy program over a period of four years through the eyes of mothers of young children from four diverse communities. It focuses on their reported perceptions of the program and related practices. Better Beginnings, which involves strong cooperation between health professionals, local government and public libraries, was developed by the State Library of Western Australia to encourage parents to share books, songs and rhymes with their babies and young children. The mothers responded to four annual surveys, in which they were asked about their perceptions of the program and its influence on literacy practices and beliefs. Overall, results showed that these mothers reported that they were highly positive about the program; were confident in and valued book-sharing activities; shared books on a regular basis, as did some other family members; and that their child was actively involved in book sharing and related activities. Of particular interest were the mothers' reports of their changing practices as their child matured over the four years of the study and also their child's language- and literacy-related behaviours. Many mothers attributed these changes in practices and behaviours to the Better Beginnings program and gave valuable evaluative feedback for modifications to the program, which has informed its further development.